Enabling high surface and space utilization of activated carbon for supercapacitors by homogeneous activation. (September 2021) - Jiang, Yuting; Jiang, Zimu; Shi, Mengjiao; Liu, Zheng; Liang, Shichuan; Feng, Jing; Sheng, Rui; Zhang, Su; Wei, Tong; Fan, Zhuangjun
Abstract: Improving both surface and space utilization of active carbon is crucial for compact supercapacitors. Herein, two activated carbons are prepared through homogeneous activation (HAC) and traditional outside-in activation (OIAC). Compared with OIAC with deep and branched porous structure, HAC shows an interconnected porous structure, leading to higher density, better gravimetric and volumetric capacitances, and improved rate performance. The results demonstrate that interconnected porous structure by homogeneous activation promotes high surface and space utilization as well as robust ion transport kinetics of activated carbon for capacitive energy storage. Graphical abstract: Activated carbon prepared by homogeneous activation shows an interconnected porous structure, enabling high surface and space utilization as well as robust electrochemical kinetics for supercapacitor electrodes. Image 1 Highlights: Homogeneous activation makes interconnected porous structure. The structure allows high surface and space utilization of activated carbon. Improved rate performance is due to robust ion transport.